2004
DOI: 10.1103/physrevlett.93.191802
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for DirectCPViolation inB0K+πDecays

Abstract: We report evidence for direct CP violation in the decay B0-->K+pi(-) with 253 fb(-1) of data collected with the Belle detector at the KEKB e(+)e(-) collider. Using 275x10(6) BB pairs we observe a B-->K+/-pi(-/+) signal with 2140+/-53 events. The measured CP violating asymmetry is A(CP)(K+pi(-))=-0.101+/-0.025(stat)+/-0.005(syst), corresponding to a significance of 3.9sigma including systematics. We also search for CP violation in the decays B+-->K+pi(0) and B+-->pi(+)pi(0). The measured CP violating asymmetrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Here there is a clear excess of events above the non-J/ψ and/or non-DD backgrounds that are reliably determined from J/ψ and D mass sideband data and shown as a hatched histogram. Chao suggested that this event excess is due to the χ ′ c0 [21]. The Belle fit to this excess, shown in the figure as a solid curve, returned a signal with a statistical significance of 3.8σ and a mass and width of M = 3878 ± 48 MeV and Γ = 347 +316 −143 MeV, which are consistent with the Guo-Meissner fit values discussed above.…”
Section: Discussionsupporting
confidence: 82%
“…Here there is a clear excess of events above the non-J/ψ and/or non-DD backgrounds that are reliably determined from J/ψ and D mass sideband data and shown as a hatched histogram. Chao suggested that this event excess is due to the χ ′ c0 [21]. The Belle fit to this excess, shown in the figure as a solid curve, returned a signal with a statistical significance of 3.8σ and a mass and width of M = 3878 ± 48 MeV and Γ = 347 +316 −143 MeV, which are consistent with the Guo-Meissner fit values discussed above.…”
Section: Discussionsupporting
confidence: 82%
“…Concerning baryonic modes, no significant effects have been observed in either B AE → ppK AE or B AE → ppπ AE decays [13]. Large CP-violating asymmetries have also been observed in charmless two-body B-meson decays such as [14][15][16]. Some recent effort has been made to understand the origin of the large asymmetries.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…In Ref. [22], Chao ruled out the interpretations of the X(4160) as the ψ(4160) or D-wave charmonium state 2 1 D 2 with J P C = 2 −+ based on NRQCD calculations and proposed the X(4160) as a candidate of the η c (4S). However, the η c (4S) assignment for the X(4160) was in conflict with the mass and decay width predictions for η c (4S) state [7,23,24].…”
Section: Introductionmentioning
confidence: 99%